Hepatitis B virus mother‐to‐child transmission among HIV‐infected women receiving lamivudine‐containing antiretroviral regimens during pregnancy and breastfeeding. Issue 3 (1st September 2014) - Pirillo, M. F.; Scarcella, P.; Andreotti, M.; Jere, H.; Buonomo, E.; Sagno, J.‐B.; Amici, R.; Mancini, M. G.; Leone, P.; Ceffa, S.; Mancinelli, S.; Marazzi, M. C.; et al.
Summary The study included 309 HIV‐infected pregnant women receiving a lamivudine‐containing antiretroviral regimen from week 25 of gestational age until 6 months postpartum, during breastfeeding. Twenty‐seven of them (8.7%) were hepatitis B virus surface antigen (HBsAg) positive; at baseline, hepatitis B virus (HBV) DNA levels >3 log10 IU/mL (with a median level of 6.2 log10 IU/mL) were found in 10 women, who at one, three and six months postpartum had median levels of 5.2 log10 IU/mL, 4.5 log10 IU/mL and 2.8 log10 IU/mL, respectively. Twenty‐four of the 30 breast milk samples evaluated had undetectable HBV DNA and the other six had values between 15 and 155 IU/mL. Median lamivudine concentrations were 1070 ng/mL in serum and 684 ng/mL in breast milk. Among the 24 HBV‐exposed children with available samples, 16 always tested negative, four had a transient infection, one had an undetermined status and three (12.5%) first tested positive at Month 12 or Month 24. Among the children born to the HBV‐uninfected mothers of the same cohort, the rate of HBsAg positivity at 12–24 months was 2% (4/196). Our finding of the absence of significative levels of HBV DNA in the breast milk of co‐infected mothers supports the present recommendations for breastfeeding in HBV‐infected women. Horizontal transmission can be hypothesized for the infections detected in children at 12–24 months. Children born to HBV‐positive mothers remained at higher risk of postnatal HBV acquisition compared to those born to HBV‐negative women.